A Morphometric Study of Nasal Index among Owo Indigenes of Ondo State, Nigeria - Okoro, Godswill Ogheneyebrorue; Igabari, John N; Owhefere, Great O (International Journal of Human and Health Sciences (IJHHS), 2024)
Objective: The purpose of this study was to investigate the morphometric characteristics of the nasal index among the Yoruba people of Owo, in Ondo State of Southern Nigeria, and to ascertain whether there is sexual dimorphism in their nasal characteristics. Methods: The study adopted the multistage, descriptive, cross-sectional survey design. A random sample of 130 males and 130 females between the ages of 18 – 55 years was taken.For each subject, the nasal height was measured and recorded as distance between nasion and subnasale while the nasal width was measured and recorded as distance between the most lateral points of right and left ala of the nose using a sliding digital caliper. Data obtained were analysed using both descriptive statistics (Mean and Standard deviation) and inferential statistics (t-test) to describe the nature of the data. Results: Data analyses showed that the mean nasal height was 42.34 ± 0.54 for males and 42.14 ± 0.56 for females and that the difference was statistically significant (p< 0.05). The mean nasal width was 40.77 ± 0.85 for males and 40.41 ± 0.42 for females and that the difference was statistically significant (p<0.05). The mean nasal index was 96.68 ± 2.91 for males and 95.43 ± 1.66 for females, and that the difference between both groups was statistically significant (p<0.05). Among the male respondents, 3.8%, 24.6% and 71.5%exhibited the Leptorrhine, Mesorrhine and Platyrrhine nose types, while for the female respondents, the respective proportions were 5.4%, 28.5% and 66.1% for Leptorrhine, Mesorrhine and Platyrrhine nose types. Conclusion: We observed sexual dimorphism in the nasal characteristics of Owo indigenes in Nigeria and the Platyrrhine type of nose was prevalent among them. International Journal of Human and Health Sciences Vol. 08 No. 02 Apr’24 Page: 165-169